Fertility sparing surgery in sex-cord stromal tumors: oncological and reproductive outcomes. Issue 8 (18th April 2022) - Bergamini, Alice; Luisa, Fais Maria; Dellino, Miriam; Erica, Silvestri; Loizzi, Vera; Bocciolone, Luca; Rabaiotti, Emanuela; Cioffi, Raffaella; Sabetta, Giulia; Cormio, Gennaro; Mangili, Giorgia
Abstract : Sex cord stromal tumors are rare neoplasms, frequently diagnosed in young women often as early-stage disease. In patients who desire to preserve fertility, when possible, unilateral salpingo-oophorectomy with peritoneal surgical staging is a safe alternative to radical treatment. In this review, we analyze the available literature on the obstetrical outcomes after fertility-sparing surgery in a total of 255 patients with sex cord stromal tumors. We found that the spontaneous conception rate in granulosa cells tumor is encouraging (88.5%). In particular, juvenile granulosa cell tumors are associated with a more successful pregnancy rate than adult granulosa cells tumors (11/26 (42.3%) in juvenile granulosa cells tumors compared with 28.5% in adult granulosa cell tumors, respectively.) On the other hand, the results of obstetrical outcomes in Sertoli-Leydig cells tumors are less promising (7/36 (19.4%)). Unfortunately, no evidence on this topic is available for sex cord tumor with annular tubules due to the low incidence. Regarding the oncological outcomes of 900 cases of sex cord stromal tumors treated conservatively, data are reassuring with comparable outcomes between patients treated with conservative and radical surgery. Given the limited available data on this rare tumor, further studies are needed to evaluate the safety of conservative approaches and to define the obstetrical outcomes in this patient population.